The Geography of Transport Systems - Rodrigue, Jean-Paul (Routledge, 2024)
This expanded and revised sixth edition of The Geography of Transport Systems provides a comprehensive and accessible introduction to the field with a broad overview of its concepts, methods, and areas of application. It explores the spatial aspects of transportation and focuses on how the mobility of passengers and freight is linked with geography. The book is divided into ten chapters, each covering a specific conceptual dimension, including networks, modes, terminals, freight transportation, urban transportation, and environmental impacts, and updated with the latest information available. The sixth edition offers new and updated material on information technologies and mobility, e-commerce, transport and the economy, mobility and society, supply chains, security, pandemics, energy and the environment, and climate change. With over 140 updated figures and maps, The Geography of Transport Systems presents transportation systems at different scales ranging from global to local. This volume is an essential resource for undergraduates studying transportation, as well as those interested in economic and urban geography, transport planning and engineering. A companion website, which contains additional material such as photographs, maps, figures, and PowerPoint presentations, has been developed for the book and can be found here: https://transportgeography.org/"